URGENSI ILM AL-MAANIY DALAM MENGISTIMBATKAN HUKUM - Wahyuddin, Wahyuddin (Universitas Islam Negeri Antasari Banjarmasin, 2013)
One of the causes of the the difference between them in understanding the meanings contained in a word ultimately lead to different interpretations. 'Ilm al-ma'aniy strongly associated with three elements. The first, which convey an idea, secondly, that receive or hear an idea, and third, the condition to convey an idea, who receive or hear an idea. A text cannot be separated from the three elements that convey the text itself, which is received or read the text and the context in which the text was delivered. This is one side lies the significance of the theories (rules) 'ilm al-ma'aniy to resolve legal. on the other side, the Koran is not uncommon uslub (style) that experienced the deviation, like a textual (lafzhiy) uslub shaped al-khabar, but contextually (ma'nawiy) it requires understanding uslub al insya '. Nor vice versa sometimes there are textual Qur'anic verses (lafzhiy) uslub al-insyak shaped, but contextually (ma'nawiy) it requires understanding uslub al-khabar.